Dietary Patterns in the Military Orders in the East and West during the Middle Ages. The Use of Meat - Salerno, Mariarosaria (Revue d'histoire ecclésiastique, 2025)
The theme of dietary patterns and mainly the use of meat and its prohibitions —as an "indicator" element in the daily life and diet of Christians and especially of monastics— takes on a rich significance for the history and knowledge of the Military Orders. This study may be useful for highlighting the dietary attitudes and meat consumption of this new type of Religio, characterised by the complete integration between the monastic model of life and the military and hospitaller model. Its peculiarities and differences from other religious orders —which were also "inspirers" of certain charisms— will be brought into focus, with particular attention to the Templars and the Hospitallers of St. John of Jerusalem. Le thème des habitudes alimentaires, et plus particulièrement de la consommation de viande et de ses interdictions — en tant qu’élément « indicatif » dans la vie quotidienne et le régime alimentaire des chrétiens et surtout des religieux — revêt une importance capitale pour l’histoire et la compréhension des ordres militaires. Cette étude peut être utile pour mettre en évidence les attitudes alimentaires et la consommation de viande au sein de ce nouveau type de Religio, où le mode de vie monastique s’intègre pleinement aux principes militaires et hospitaliers. Ses spécificités et ses différences par rapport à d’autres ordres religieux — également « sources d’inspiration » pour certains charismes — seront mises en lumière, avec une attention particulière portée aux Templiers et aux Hospitaliers de St-Jean de Jérusalem. Das Thema des Ernährungsmusters, und dabei hauptsächlich des Gebrauches von Fleisch und dessen Verbotes, als indikatives Element im täglichen Leben und der Diät von Christen, insbesondere religiösen, ist bedeutungsvoll für die Geschichte und Kenntnis der Militärorden. Diese Studie kann einen Beitrag dazu leisten, Ernährungsansichten und Fleischkonsumption dieses neuen Typus einer "Religio" auszuleuchten, der von einem allumfassenden Verband zwischen dem monastischen Lebensmodell und dem Modell der Militärund Johanniterorden charakterisiert wird. Seine Eigenheiten und Unterschiede zu anderen Orden - die ebenso Inspiration für gewisse Charismen waren - werden, unter besonderer Berücksichtigung des Templerordens und der Johanniter, ins Blickfeld gestellt.